Patterns of species richness and vegetative performance in heath ecosystems at Thingvellir, Southwest Iceland - Jägerbrand, Annika (Botanical Institute, Göteborg University, Göteborg, Sweden, 2004)
The Racomitrium lanuginosum (Hedw.) Brid. moss heath is a unique environment and is of great importance for co-occurring established vascular plants. A thick moss carpet can prevent or restrict the growth of vascular plants as they are exposed to more unfavourable growth conditions, but the effect on species richness and abundance is less known. To investigate the negative effects of a well-developed moss carpet on established vascular plants, patterns of species richness, shoot density, and number of leaves (Carex bigelowii Schwein. and Thalictrum alpinum L.) were studied in two different vegetation types, Racomitrium lanuginosum moss heath, and dwarf shrub heath in Þingvellir National Park, Southwest Iceland. Species richness was higher in dwarf shrub heath and increased proportionally with the size of the shrub patches. Total species richness and plant functional dominance did not differ between vegetation types. There were no differences found in shoot density, percentage of flowering and juveniles, number of leaves in Carex bigelowii, or shoot density, flowering percentage or number of leaves in Thalictrum alpinum between the vegetation types. However, leaf length of Carex bigelowii was higher in the dwarf shrubs heath, indicating more favourable growth conditions, shade or shelter effects. It is possible that translocation is taking place between the shoots of the clonal vascular plants in this study so that the plants themselves are counteracting unfavourable effects in the different vegetation types. The effect of global climatic change on moss heaths in Iceland is briefly discussed.